ANALISIS ANCAMAN DAN PELUANG PONDOK PESANTREN Al-HAMIDY LOMBOK BARAT PASCA UNDANG-UNDANG PESANTREN MELALUI METODE ANALISIS SWOT - Fauzi, Muhamad Iwan; Fadli, Adi; Wahyudiati, Dwi (Dharmas Education Journal (DE_Journal), 2024)
The research aims to conduct a SWOT analysis of the Al-Hamidy Kebon Talo Islamic Boarding School after the Islamic Boarding School Law in West Lombok. SWOT analysis was carried out to analyze the opportunities and threats faced by the Al Hamidy Islamic boarding school after the implementation of the Islamic Boarding School Law. The research approach used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. Meanwhile, technical data analysis uses data collection, data reduction, data presentation and data verification. Research respondents included Islamic boarding school leaders, teachers, students and other relevant stakeholders. The research results show that ( 1) Al-Hamidy Islamic Boarding School has several opportunities, including the implementation of the Islamic Boarding School Law opens up new opportunities for Islamic boarding schools to obtain assistance and support from the government as well as increasing accreditation and official recognition of Islamic boarding schools . (2) Al-Hamidy Islamic Boarding School has several threats, such as competition with other educational institutions, changes in regulations, and the potential influence of extremist understandings of Islam